A Trace Metals, Radiobiology, and Cancer Information Retrieval System (Tracirs) - Lunin, Lois F. (Methods of Information in Medicine, 1965)
A method is described which was designed to retrieve key facts as well as references in a computer-based pathology information system. The facts appear in the form of miniature abstracts which also serve as a machine-searchable index. This combined index-abstract provides a form suitable both for computer storage and retrieval as well as for a desk reference guide. One product of the system is the pilot edition of the Trace Metals Literature Index-Handbook which supplies data and references on elements, mostly trace metals, as they may be related to normal and pathologic conditions.